Pin Rileks, Tenang, Damai (RTD) dalam Terapi Mind Healing Technique (MHT) Perspektif Tasawuf - Khodijah Robiah Al Adawiyah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the pin Relax, Calm, Peaceful (RTD) in the Mind Healing Technique (MHT) therapy from the perspective of Sufism. This research is included in the type of qualitative research by applying the literature study method. Sources of research data include primary sources and secondary sources. The primary data source of this study is the results of observing Relax, Calm, Peaceful (RTD) pins in the Mind Healing Technique (MHT) therapy from a tasawuf perspective. Meanwhile, secondary data sources are literature related to this research topic, including journal articles, books, and others. The results and discussion obtained from this study are that the conditions in the calm pin and peace pin on the Relax, Calm, Peaceful (RTD) pin in the Mind Healing Technique (MHT) therapy from a tasawuf perspective have similarities with the concept of self-purification methods of the Sufis. The conclusion drawn from this study is that the Relax, Calm, Peaceful (RTD) pin in Mind Healing Technique (MHT) therapy has similarities with the concepts of takhalli, tahalli, and tajalli in the perspective of Sufism.